Huoxiang Zhengqi dropping pills alleviate exertional heat stroke–induced multiple organ injury through sustaining intestinal homeostasis via regulating MAPK/NF-κB pathway and gut microbiota in rats - Lei Li; Lei Li; Lei Li; Jun Ma; Jun Ma; Zeshi Li; Zeshi Li; Juelin Chen; Jiawei Zhou; Yawei Wang; Yankun Pei; Yitong Gong; et al. (Frontiers in Pharmacology)
Exertional heat stroke (EHS) is a life-threatening condition characterized by hyperthermia and multi-organ dysfunction, often associated with intestinal barrier disruption. This study evaluated the protective effects of Huoxiang Zhengqi Dropping Pills (HXZQD) against EHS in a rat model. HXZQD was administered via oral gavage at low, medium, and high doses, followed by EHS induction through exercise under high-temperature and high-humidity conditions. The findings revealed that high-dose HXZQD significantly delayed the onset of EHS, reduced core body temperature elevations, and mitigated multi-organ injury, as evidenced by biochemical markers and histopathological examination. This study showed that HXZQD alleviated EHS-induced intestinal damage by preserving barrier proteins (ZO-1, Occludin, and Ecadherin) and maintaining intestinal barrier integrity. Transmission electron microscopy confirmed the preservation of tight junction structures. Further analysis indicated that HXZQD modulated the MAPK/NF-κB signaling pathways, inhibiting heat stress-induced activation and reducing inflammation. Additionally, HXZQD positively regulated gut microbiota, increasing the proportion of beneficial Lactococcus and decreasing harmful Streptococcus. These findings suggest that HXZQD maintains intestinal homeostasis during EHS by preserving barrier function and modulating gut microbiota, offering a promising preventive approach for EHS management.